1980
DOI: 10.1055/s-2008-1074929
|View full text |Cite
|
Sign up to set email alerts
|

HPLC Separation and Quantitative Determination of Ginsenosides from Panax ginseng, Panax quinquefolium and from Ginseng Drug Preparations

Abstract: A new HPLC-method for separation and quantitative determination of ginsenosides in Panax ginseng, Panax quinquefolium and in pharmaceutical drug preparations is elaborated. A reversedphase-system with pBondapak C18 column (3.9 mm I. D . x 30 cm) using acetonitrile-water (30:70) 2 ml/min and acetonitrile-water (18:82) 4 ml/min is suitable for the base-line separation of Rb,, Rbz, Rc, Rd, Rf, R k , respectively Re, Rg, in 30 minutes. The ginsenosides are directly detected at 203 nm (without derivatization) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(74 citation statements)
references
References 0 publications
6
67
1
Order By: Relevance
“…The concentrations determined by ELISA agreed well with those determined by HPLC (Kitagawa et al, 1987). ELISA was more sensitive than TLC (Tani et al, 1981) or HPLC (Sticher and Sticher, 1979;Soldati and Sticher, 1980). Moreover, Yamaguchi et al (1988) and Samukawa et al (1995) reported the comparative concentrations of ginsenosides in various commercial ginseng radices analyzed by HPLC.…”
Section: G-rb1 and -Rg1 Concentrations In Panax Spp Measured By Elisasupporting
confidence: 66%
“…The concentrations determined by ELISA agreed well with those determined by HPLC (Kitagawa et al, 1987). ELISA was more sensitive than TLC (Tani et al, 1981) or HPLC (Sticher and Sticher, 1979;Soldati and Sticher, 1980). Moreover, Yamaguchi et al (1988) and Samukawa et al (1995) reported the comparative concentrations of ginsenosides in various commercial ginseng radices analyzed by HPLC.…”
Section: G-rb1 and -Rg1 Concentrations In Panax Spp Measured By Elisasupporting
confidence: 66%
“…The detection limits of these ginsenosides were 0.033-0.056 mg (calculated into mg unit) in this study. The detection limits of these ginsenosides were reported to be 0.3 mg by Soldati et al 18) and 0.09-0.20 mg by Samukawa et al 19) Therefore, our method was excellent with regard to detection ability of ginsenosides.…”
Section: Resultsmentioning
confidence: 73%
“…GI 15 represents as active principles 4% of the specific for ginseng triterpene saponins called ginsenosides (Sticher and Soldati, 1979;Soldati and Sticher, 1980;Schulten and Soldati, 198 I).…”
Section: Methodsmentioning
confidence: 99%